In-vitro and In-vivo Evaluation of Antiarthritic, Anti-inflammatory and Analgesic Effect of Nanoemulsion loaded with Crinum latifolium leaves extract - Ankur Sharma, Saloni Kakkar, Shaveta Ahalwat, Vikas Jogpal, Rahul Singh (South Eastern European Journal of Public Health, 2025)
This study explores the therapeutic potential of a nanoemulsion formulated with Crinum latifolium leaf extract for its anti-arthritic, anti-inflammatory, and analgesic effects. Stability and particle size distribution were also characterized. In-vivo evaluations included CFA-induced arthritis, carrageenan-induced paw edema for inflammation assessment, and Eddy’s hotplate test for analgesic effects. Invitro study of nanoemulsion showed potent antioxidant activity and inhibited hyaluronidase enzyme by 75.05%, indicating its role in preventing joint degradation. At a 1 mg/kg dose in the CFA-induced arthritis model, the nanoemulsion significantly reduced paw edema by 64.28%, comparable to standard treatment. Body weight analysis showed an increase from 187.83 ± 2.89 g to 230.32 ± 9.33 g, suggesting overall health improvement. Hematological parameters were normalized, with a marked reduction in ESR from 8.40 ± 0.33 mm/h to 1.76 ± 0.30 mm/h, indicating reduced inflammation. Histopathological examination confirmed reduced synovial hyperplasia, inflammatory cell infiltration, and cartilage damage. Additionally, the nanoemulsion enhanced pain tolerance, showing a 45.45% increase in pain threshold in Eddy’s hotplate test. These findings highlight the nanoemulsion’s therapeutic potential for arthritis management, warranting further research into its clinical application.